P-003 Baseline DWI volume predicts successful recanalization in multimodal endovascular therapy for acute ischemic stroke. (4th July 2012) - Raychev, R; Liebeskind, D; Saver, J; Hao, Q; Vinuela, F; Tateshima, S; Jahan, R; Gonzalez, N; Szeder, V; Cramer, R; Balugde, A; Rastogi, S; et al.
Abstract : Background: Effective reperfusion is associated with better outcome from acute cerebral ischemia. The pre-intervention clinical and imaging predictors of procedural success in patients treated with multimodal mechanical device strategies (Merci ± Penumbra ± angioplasty and stenting) have not been well delineated. Methods: In a prospectively maintained database, we analyzed consecutive patients with acute ICA and M1 occlusions treated with endovascular recanalization following MRI. We investigated the pretreatment clinical and imaging factors associated with substantial recanalization (TICI≥2b) and clinical outcome. Results: Among 105 patients meeting study entry criteria, mean age was 66.6 (±17.8). 65 % were female, median pretreatment NIHSS was 18 (range 2–31), mean baseline DWI volume was 30.6 cc (SD±35.1), and mean time to groin puncture was 412 min (SD±207.6). The median number of mechanical device passes was two (range 0–8). 73 (70%) patients were treated with a single device. IV tPA was used in 43 patients (41%). Substantial recanalization occurred in 43 patients (41%). The strongest predictors of poor outcome (mRS >3 at discharge) were high baseline NIHSS (OR 0.87; p<0.001) and presence of SAH after the procedure (OR 0.05; p=0.001). However, the presence of SAH did not correlate with the number of attempts or devices used. The strongest predictor of better outcome at discharge (mRS ≤3) was substantial recanalization (TICI≥2b). Time to groin puncture, number of device passes, single vs multiple device therapy, adjunctive IV TPA, or arterial occlusion site did not correlate substantial recanalization. In the final logistic regression multivariate analysis, among all baseline clinical and imaging variables considered, the pre-treatment DWI volume was the only factor associated with a substantial recanalization (OR 0.238; p=0.046). Conclusions: Baseline DWI lesion volume is a potent predictor of substantial reperfusion in multimodal endovascular therapy for acute ischemic stroke. This finding suggests that the effectiveness of the reperfusion therapy is likely influenced by much more complex pathophysiological mechanism, rather than mechanical and/or anatomical factors alone. Competing interests: None.